Communication of the cancer diagnosis to an elderly patient - Lucélia Terra Jonas; Natália Michelato Silva; Juliana Maria de Paula; Sueli Marques; Luciana Kusumota (Universidade Federal do Ceará, 2015)
Objective: to collect evidence on matters which involve cancer diagnosis disclosure to an elderly patient. Methods: integrative revision made in five important data bases in the area of health with seven selected articles. Results: it was noticeable that there are conflicts between family members and health professionals concerning cancer diagnosis disclosure to an elderly patient and that the preferences of those people on the disclosure of the diagnosis are similar to other patients. Conclusion: health professionals, especially the nurses, need training in order to have a secure and clarifying communication, matching the information to the specific needs of each patient, considering their reality and type of confrontation..